ANALYSIS OF ARITHMETIC DIFFICULTIES AMONG ELEMENTARY SCHOOL STUDENTS - Enda Lovita Pandiangan; Dian Anggeraini; Nurul Putri Aulia; Maulida Khairunnisa; Vira Marsella (Universitas Islam Negeri Mataram, 2024)
This study aims to identify the learning difficulties of grade VI students in arithmetic at MIS YPII Tanjung Pura and analyze the factors influencing these difficulties. A quantitative method with a descriptive approach was employed for data collection through questionnaires and analysis of student scores. The questionnaire consisted of 20 statements with